Accuracy of iodine quantification in dual-layer spectral CT: Influence of iterative reconstruction, patient habitus and tube parameters. Issue 102 (May 2018) - Sauter, Andreas P.; Kopp, Felix K.; Münzel, Daniela; Dangelmaier, Julia; Renz, Martin; Renger, Bernhard; Braren, Rickmer; Fingerle, Alexander A.; Rummeny, Ernst J.; Noël, Peter B.
Abstract: Purpose: Evaluation of the influence of iterative reconstruction, tube settings and patient habitus on the accuracy of iodine quantification with dual-layer spectral CT (DL-CT). Material and methods: A CT abdomen phantom with different extension rings and four iodine inserts (1, 2, 5 and 10 mg/ml) was scanned on a DL-CT. The phantom was scanned with tube-voltages of 120 and 140 kVp and CTDIvol of 2.5, 5, 10 and 20 mGy. Reconstructions were performed for eight levels of iterative reconstruction (i0-i7). Diagnostic dose levels are classified depending on patient-size and radiation dose. Results: Measurements of iodine concentration showed accurate and reliable results. Taking all CTDIvol -levels into account, the mean absolute percentage difference (MAPD) showed less accuracy for low CTDIvol -levels (2.5 mGy: 34.72%) than for high CTDIvol -levels (20 mGy: 5.89%). At diagnostic dose levels, accurate quantification of iodine was possible (MAPD 3.38%). Level of iterative reconstruction did not significantly influence iodine measurements. Iodine quantification worked more accurately at a tube voltage of 140 kVp. Phantom size had a considerable effect only at low-dose-levels; at diagnostic dose levels the effect of phantom size decreased (MAPD <5% for all phantom sizes). Conclusion: With DL-CT, even low iodine concentrations can be accurately quantified. Accuracies are higher when diagnostic radiation doses are employed.